Cross-sectional Study of Multiple Antibiotic-resistant Streptococcus suis in Pigs and Environs - Iheukwumere, I. H.; Iheukwumere, M. C. (IPS Interdisciplinary Journal of Biological Sciences, 2022)
Streptococcus suis; a dominant specie found in pigs and environs, has been receiving drastically attention not only in causing human infections but also for its involvement in antibiotic resistance, of which 80% of these resistant genes are encoded in the plasmid. This study was undertaken to evaluate the resistance of different strains of Streptococcus suis isolated from the pigs and environs against conventional antibiotics. Samples were collected from different anatomical sites of the pigs and their environs and screened for the presence of Streptococcus suis using standard microbiological techniques. The resistant strains were detected by subjecting the isolates to an antibiotic susceptibility test using the disk diffusion method. The study revealed the presence of Streptococcus suis Q, Streptococcus suis R, Streptococcus suis S and Streptococcus suis Y, of which 24.14%, 100.00%, 41.67% and 39.23% of isolates Q, R, S and Y respectively that were resistant to antibiotics; 64.29%, 100.00% and 63.64% were multiple antibiotic resistant (MAR) strains, and 61.76% of the resistant strains had MAR index greater than 0.2. From the above study, different strains of multiple antibiotic-resistant Streptococcus suis were isolated from pigs and environs, of which isolate Q was most predominant, especially in nasal samples.